Entrepreneurship Education Scenario in India: A Study - Gandhi Shraddha Rajnikant (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
The importance of entrepreneurship education for educated young cannot be overstated. However, educated young from rural regions continue to move to cities in quest of work, and the number of educated jobless is growing by the day. Furthermore, individuals who have left educational institutions may be unable to find a job that pays a fair wage. As a result, educational institutions should use entrepreneurial teaching methods to promote student self-reliance and convince them with creative ideas, new enterprises, and new approaches to meet global problems in the face of changing demand. The traditional ways of teaching entrepreneurial education must be thrown away as soon as possible. The new entrepreneurship education teaching techniques encourage students to become entrepreneurs. As a result, the emphasis of this article is on the need for entrepreneurship education teaching techniques that would encourage students in India to become entrepreneurs.